(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Mulk Raj Anand, through his rare prolificacy, boldexperimentation and aesthetic sensibility, has made immense contribution toIndian as well as world literature in English. His choice of unconventionalsubjects and characters has been determined by his Dickensian humanisticphilosophy. He set up new trends by introducing negative hero and/or anti-heroin his novels. His fictional world is peopled by characters from various strataof society- from the lowest to the highest rungs in the hierarchy. Anand hasrevealed exceptional, psychological insight in the portrayal of thesecharacters who “once were real men and women” and are not mere phantoms offantasy. However, his otherwise authentic and objective delineation ofcharacter is superb which the chief requisite of a work of art is. This paperpresents a confrontation and interaction between Anand’s métier as an artist asa compelling demand of his humanistic creed. Not that humanism is, in any way,contrary to art. It will not be far from truth to assert that all is, atbottom, humanistic even though not expressly “a criticism of life”. Thegreatness of an artist lies in synthesizing art and reality. When he handlesreality imaginatively and presents it artistically, the result is greataesthetic delight both for the reader and the artist but it is when humanismobsesses the mind of the artist so strongly that he is ready to make out subservant to his philosophy, that the artist’s failure starts. The present paperdiscusses the oscillation of Anand between his integrity as an artist and hisenthusiasm as a reformist.